Table of Content - - (Journal of Humanities & Social Sciences, 2023)
1. Natural disasters and their effects in Jerusalem in the Mamluk era (648 – 923 AH 1250 – 1516 AD) Mr. Hmydan Mahmoud Naji 2. The aesthetic of Arabic calligraphy in Saudi plastic painting Co-Prof. Maha Mohammed Alsudairy 3. The impact of the COVID-19 pandemic on the females’ Intention to buy clothes Online in Makkah region Mrs. Tahany Abdullah Abdul-Baqi Elias , Dr. Tagreed Saleh Ali Abalkhail 4. The Reality of the Qatari Family and the Challenges Faced An Inter-generational Qualitative Study Mrs. Afrah Farhan Al-Otaibi , Mrs. Noura Hamad Al-Hajry , Mrs. Sarah Ali Al-Sallabi , Dr. Asmaa Malkawi 5. Assessment of sustainable development in the urban poles status of the urban pole Retba (Municipality of Didouche Mourad-Constantine) Mrs. Haouari Souad 6. The stance of Uday bin Hatim from the political developments in the Rashidi period Mr. Bader Haif bin Omerah 7. The role of the medical social worker with patients with Complicated Grief disorder Lecturer Norah Farhan Al-Anazi , Co-Prof. Husain Mohammed Al-Hakami